BINA DESA 2025: Pelatihan Produksi Konten dan Multimedia sebagai Upaya menjadi Citizen Journalist di Kampung Pekijing - Ardelia Citra Dewi; Bangun Yoga Wibowo; Siti Muhibah (Pusat Riset dan Inovasi Nasional, 2026)
The 2025 Bina Desa activity is a community service program aimed at enhancing the capacity of the youth in Kampung Pekijing in content and multimedia production as an effort to strengthen the role of citizen journalists. Kampung Pekijing has the potential to become a Literacy Tourism Village, but it is not yet supported by adequate digital promotion skills among the local community, especially the younger generation. This activity begins with a series of field observations to identify the needs and main issues of the village, which then serve as the basis for designing the training program. The implementation method uses participatory training that combines material delivery, discussions, interactive quizzes, and hands-on content production practice. The training is conducted in two stages, focusing on strengthening the understanding of content concepts, basic photography and videography techniques, up to the practice of creating and editing videos in a contextual manner. The results of the activity indicate an increase in participants' knowledge and skills in producing digital content, marked by their ability to independently create video content. In addition, participants showed a positive response to the material and training methods applied. Although there were some technical obstacles and time limitations, this activity demonstrated that practice-based and locally contextualized training is effective in encouraging youth engagement as citizen journalists to support the branding of Kampung Pekijing.